Graphene oxide/manganese ferrite nanohybrids for magnetic resonance imaging, photothermal therapy and drug delivery. (January 2016) - Yang, Yan; Shi, Haili; Wang, Yapei; Shi, Benzhao; Guo, Linlin; Wu, Dongmei; Yang, Shiping; Wu, Huixia
Superparamagnetic manganese ferrite (MnFe2 O4 ) nanoparticles have been deposited on graphene oxide (GO) by the thermal decomposition of manganese (II) acetylacetonate and iron (III) acetylacetonate precursors in triethylene glycol. The resulting GO/MnFe2 O4 nanohybrids show very low cytotoxicity, negligible hemolytic activity, and imperceptible in vivo toxicity. In vitro and in vivo magnetic resonance imaging experiments demonstrate that GO/MnFe2 O4 nanohybrids could be used as an effective T2 contrast agent. The strong optical absorbance in the near-infrared (NIR) region and good photothermal stability of GO/MnFe2 O4 nanohybrids result in the highly efficient photothermal ablation of cancer cells. GO/MnFe2 O4 nanohybrids can be further loaded with doxorubicin (DOX) by π–π conjugate effect for chemotherapy. DOX release from GO/MnFe2 O4 is significantly influenced by pH and can be triggered by NIR laser. The enhanced cancer cell killing by GO/MnFe2 O4 /DOX composites has been achieved when irradiated with near-infrared light, suggesting that the nanohybrids could deliver both DOX chemotherapy and photothermal therapy with a synergistic effect.